Arriving at the Convenient Rays for Locating Image formed by a Spherical Mirror using Ray Tracing Technique and Verification of Mirror Formula by Graphical Method - Koireng, R.R. (SCHOOL SCIENCE, 2015)
In this paper, the convenient rays for locating image formed by spherical mirrors using ray tracing technique are discussed. Only concave mirror is taken for the purpose of illustration and simplification. Ray tracing technique is used to locate images formed by concave mirrors using graphical method. The mirror formula is verified empirically using graphical method by measuring the values of image distance, object distance and focal length of the concave mirror. This technique of finding the image formed by a concave mirror using ray tracing technique by graphical method was used in teacher training programmes and it is being published for wider dissemination.